The 3' ends of human pre-snRNAs are produced by RNA polymerase II CTD-dependent RNA processing. - Uguen, P; Murphy, S (2003)
Proper 3' end formation of the human pre-snRNAs synthesized by pol II requires the cis-acting 3' box, although the precise function of this element has proved difficult to determine. In vivo, 3' end formation is tightly linked to transcription. However, we have now been able to obtain transcription-independent 3' box-dependent processing in vitro. This finally demonstrates that the 3' end of pre-snRNAs is produced by RNA processing rather than by termination of transcription. The phosphorylated form of the C-terminal domain (CTD) of pol II activates the processing event in vitro, consistent with our previous demonstration of the role of the CTD in pre-snRNA 3' end formation in vivo. In addition, we show that sequences upstream from the 3' box of the U2 snRNA gene influence 3' end formation both in vivo and in vitro.